Facile synthesis of size-tunable superparamagnetic/polymeric core/shell nanoparticles by metal-free atom transfer radical polymerization at ambient temperature. Issue 13 (23rd January 2017) - Wang, Xiaobing; You, Ning; Lan, Fuqiang; Fu, Peng; Cui, Zhe; Pang, Xinchang; Liu, Minying; Zhao, Qingxiang
Abstract : Size-tunable superparamagnetic/polymeric core/shell nanoparticles with uniform distribution was fabricated based on metal-free atom transfer radical polymerization at ambient temperature. Abstract : A facile route to fabricate size-tunable superparamagnetic/polymeric core/shell nanoparticles with uniform distribution was introduced based on metal-free atom transfer radical polymerization at ambient temperature.